Análise do fenômeno da declinação na entonação de frases contextualizadas dos falantes do português brasileiro - Vanessa Goncalves Ferreira (2007)
This dissertation aimed at describing declination in Brazilian Portuguese speakers by means of an regression analysis. Declination is the tendency of intonation to low towards the end of the utterance, a phenomenon commonly observed in many languages. According to the literature, declination of sentences in context is programmed by the speaker in order to indicate that an information has been concluded. We analysed a corpus of 10 coordinated sentences with 3 embedded sentences each. They were silently rehearsed and then produced by 10 Belo Horizonte speakers in a close-to-natural way. The results of ourregression analyses showed that declination always occurs in final sentences, as stated in the literature. That could be considered as a result of the speakers intention to indicate the end of the stated information. In sentences of the same linguistic content inserted betweentwo sentences in medial position declination does not occur always, indicating that the speaker plans a continuity in discourse. In conclusion, declination occurs in Brazilian Portuguese sentences in context.